Preparation method of negative electrode of lithium battery and lithium battery
The fiber membrane loading metal ions is prepared by coaxial electrospinning method, and carbonization and heat treatment are carried out to form a current collector to prepare lithium metal on its surface, solving the problem of insufficient thickness of lithium metal negative electrode material and realizing the thinness of the negative electrode of lithium battery Improve the degree and efficient utilization of lithium resources.
Patent Information
- Application Number
- CN202411541027.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The thickness of the lithium metal negative electrode material is not thin enough, resulting in an oversupply of lithium usage, an imbalance in the capacity ratio of the negative electrode material and the positive electrode material, and the low utilization rate of lithium is a waste of lithium resources.
The fiber membrane with a large amount of metal ions loaded with the shell structure was prepared by coaxial electrospinning method, carbonization and heat treatment were performed to form a current collector, and lithium metal was prepared on the surface of the current collector, and a very thin thickness of lithium battery negative electrode was obtained by pressing treatment.
The thinness of the negative electrode of lithium battery is improved, the Coulomb efficiency and cycle life of the negative electrode of lithium metal is improved, the amount of lithium is reduced, and the utilization efficiency of lithium resources is improved.
Smart Images

Figure CN119419222A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy, and in particular to lithium batteries. Background Art
[0002] The traditional negative electrode material of lithium-ion batteries is graphite, but due to its low specific capacity, the energy density of lithium-ion batteries has reached a development bottleneck. Lithium metal is considered to be the most promising negative electrode material in the next generation of high specific energy battery systems due to its advantages such as high specific capacity and low electrode potential. However, the commercial lithium foil currently available is usually very thick (the thinnest is about 50μm), resulting in a serious excess of lithium. This not only means that the capacity ratio of negative electrode materials and positive electrode materials is unbalanced, but also the utilization rate of lithium is quite low, which is a waste of lithium resources. Summary of the invention
[0003] The embodiments of the present application provide a method for preparing a negative electrode of a lithium battery and a lithium battery to solve the technical problem that the thickness of the lithium metal negative electrode material is not thin enough.
[0004] In a first aspect, an embodiment of the present application provides a method for preparing a negative electrode of a lithium battery, the method comprising the following steps:
[0005] Coaxial electrospinning is performed with a core solution and a shell solution to obtain a fiber membrane;
[0006] Carrying out carbonization treatment on the fiber membrane to obtain a carbon fiber membrane;
[0007] heat-treating the carbon fiber film in an ammonia atmosphere to obtain a current collector;
[0008] preparing lithium metal on the surface of the current collector to obtain a prefabricated negative electrode;
[0009] The prefabricated negative electrode is pressed to obtain the negative electrode of the lithium battery.
[0010] Among them, the fibers of the fiber membrane have a core structure and a shell structure, the shell structure covers the core structure, the core solution is used to form the core structure during the coaxial electrospinning process, and the shell solution is used to form the shell structure during the coaxial electrospinning process, the core solution includes a carbonizable first polymer, the shell solution includes a salt substance and a carbonizable second polymer, and the metal element of the salt substance is at least one of chromium, nickel, cobalt, manganese, iron, copper, molybdenum, and zinc.
[0011] In some embodiments of the present application, the first polymer is at least one of polyacrylonitrile, polyvinyl pyrrolidone, polyvinylidene fluoride, polycaprolactone, polyurethane, silk fibroin, polyamide, polyvinyl alcohol, polymethyl methacrylate, and asphalt; and / or,
[0012] The solvent of the core solution is at least one of water, ethanol, NN dimethylformamide, acetone, NN diethylacetamide, formic acid, tetrahydrofuran, isopropanol, and hexafluoroisopropanol; and / or,
[0013] In the core solution, the mass ratio of the first polymer to the solvent of the core solution is 1:5-12.
[0014] In some embodiments of the present application, the second polymer is at least one of polyacrylonitrile, polyvinyl pyrrolidone, polyvinylidene fluoride, polycaprolactone, polyurethane, silk fibroin, polyamide, polyvinyl alcohol, polymethyl methacrylate, and asphalt; and / or,
[0015] The solvent of the shell solution is at least one of water, ethanol, NN dimethylformamide, acetone, NN diethylacetamide, formic acid, tetrahydrofuran, isopropanol, and hexafluoroisopropanol; and / or,
[0016] In the shell solution, the mass ratio of the second polymer to the salt substance is 1:0.8-1.2; and / or,
[0017] In the shell solution, the mass ratio of the second polymer to the solvent of the shell solution is 1:4-6.
[0018] In some embodiments of the present application, the coaxial electrospinning is performed by at least one coaxial spinning needle, and averaged to each coaxial spinning needle, the process parameters of the coaxial electrospinning meet the following conditions:
[0019] Voltage is 12~20kV;
[0020] The spinning solution flow rate is 0.6-1.5 mL / h;
[0021] The receiving distance is 12 to 20 cm;
[0022] The duration is 1.8 to 2.2 hours.
[0023] In some embodiments of the present application, the temperature of the carbonization treatment is 700-900° C.; and / or,
[0024] The carbonization treatment time is 1 to 3 hours; and / or,
[0025] The carbonization treatment is performed in an inert atmosphere.
[0026] In some embodiments of the present application, before the fiber membrane is carbonized, the method further comprises the following steps:
[0027] The fiber membrane is subjected to a pre-oxidation treatment.
[0028] In some embodiments of the present application, the temperature of the pre-oxidation treatment is 200-300° C.; and / or,
[0029] The pre-oxidation treatment time is 0.5 to 1 hour; and / or,
[0030] The pre-oxidation treatment is performed in an oxygen-containing atmosphere.
[0031] In some embodiments of the present application, the temperature of the heat treatment is 400-700° C.; and / or,
[0032] The heat treatment time is 1 to 3 hours.
[0033] In some embodiments of the present application, the step of preparing lithium metal on the surface of the current collector comprises the following steps:
[0034] The current collector is immersed in molten lithium metal in an inert atmosphere.
[0035] In a second aspect, an embodiment of the present application provides a lithium battery, wherein the lithium battery comprises a lithium battery negative electrode prepared by the method described in any embodiment of the first aspect.
[0036] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0037] The method for preparing the negative electrode of a lithium battery provided in the embodiment of the present application is to prepare a fiber membrane with a shell structure loaded with a large amount of metal ions by coaxial electrospinning, and then the fiber membrane is subjected to carbonization, heat treatment in ammonia, etc. to form a current collector with a metal nitride on the surface, and then lithium metal is prepared on the surface of the current collector to obtain a prefabricated negative electrode. Since the gaps between the fibers of the current collector are large, the compressibility of the prefabricated negative electrode is very strong, and a very thin lithium battery negative electrode can be easily obtained by pressing. In addition, the current collector described in the present application also has a good affinity for lithium metal, which can effectively guide the orderly deposition and stripping of lithium metal during the charge and discharge process, inhibit the growth of lithium dendrites and the volume expansion during lithium deposition and desorption, thereby effectively improving the coulomb efficiency and cycle life of the lithium metal negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0039] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0040] Figure 1 A schematic diagram of a process for preparing a negative electrode for a lithium battery provided in an embodiment of the present application. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0042] Unless otherwise specified, the terms used herein should be understood as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. In the event of a conflict, this specification takes precedence.
[0043] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0044] Currently, there is a technical problem that lithium metal negative electrode materials are not thin enough.
[0045] The technical solution provided by the embodiments of the present application is to solve the above technical problems, and the overall idea is as follows:
[0046] In a first aspect, an embodiment of the present application provides a method for preparing a negative electrode of a lithium battery, the method comprising the following steps:
[0047] S1: Coaxial electrospinning of the core solution and the shell solution to obtain a fiber membrane;
[0048] S2: performing carbonization treatment on the fiber membrane to obtain a carbon fiber membrane;
[0049] S3: heat-treating the carbon fiber film in an ammonia atmosphere to obtain a current collector;
[0050] S4: preparing lithium metal on the surface of the current collector to obtain a prefabricated negative electrode;
[0051] S5: pressing the prefabricated negative electrode to obtain the negative electrode of the lithium battery,
[0052] Among them, the fibers of the fiber membrane have a core structure and a shell structure, the shell structure covers the core structure, the core solution is used to form the core structure during the coaxial electrospinning process, and the shell solution is used to form the shell structure during the coaxial electrospinning process, the core solution includes a carbonizable first polymer, the shell solution includes a salt substance and a carbonizable second polymer, and the metal element of the salt substance is at least one of chromium, nickel, cobalt, manganese, iron, copper, molybdenum, and zinc.
[0053] It is easy to understand that the coaxial electrospinning method is carried out through a coaxial spinning needle, which includes two coaxial capillaries with different inner diameters. The basic principle of the coaxial electrospinning method is to inject a core solution and a shell solution into a capillary with a smaller inner diameter and a capillary with a larger inner diameter, respectively, and the two converge at the end of the coaxial spinning needle, and solidify into nanofibers with a core structure and a shell structure under the action of an electric field force, wherein the shell structure covers the core structure, the core structure is formed by the core solution, and the shell structure is formed by the shell solution.
[0054] It is easy to understand that there are usually large gaps between the fibers of the electrospun fabric, and the electrospun fabric itself has a large specific surface area. The carbon fiber membrane described in the present application is made by heat treating the fiber membrane, and the fiber membrane is an electrospun fabric, which makes the current collector also have the structural characteristics of the electrospun fabric. Since the current collector has a large specific surface area, a large amount of lithium metal can be loaded on the surface of the current collector. The gaps between the fibers of the current collector are large, and lithium dendrites can also be accommodated, thereby avoiding the damage of lithium dendrites to the function of the lithium battery as much as possible. In addition, the current collector is the prefabricated skeleton, and the gaps between the fibers of the current collector are large, which makes the compressibility of the prefabricated negative electrode very strong, and it is easy to obtain a lithium battery negative electrode with a very thin thickness through a pressing process.
[0055] It is easy to understand that the shell structure carries metal ions contained in the salt substance. Heat treatment of the carbon fiber film in an ammonia atmosphere can cause these metal ions to form nitrides, which are conducive to inducing lithium metal to form crystal nuclei and have excellent affinity for lithium metal. This can effectively guide the orderly deposition and stripping of lithium metal during the charge and discharge process, inhibit the growth of lithium dendrites and the volume expansion during lithium deposition and desorption, and effectively improve the coulomb efficiency and cycle life of the lithium metal negative electrode.
[0056] The present application prepares a fiber membrane with a shell structure loaded with a large amount of metal ions by coaxial electrospinning, and then forms a current collector with a metal nitride on the surface by carbonizing the fiber membrane, heat treating in ammonia, and the like, and then prepares lithium metal on the surface of the current collector to obtain a prefabricated negative electrode. Since the gaps between the fibers of the current collector are large, the prefabricated negative electrode has strong compressibility, and a very thin lithium battery negative electrode can be easily obtained by pressing. In addition, the current collector described in the present application also has a good affinity for lithium metal, which can effectively guide the orderly deposition and stripping of lithium metal during the charge and discharge process, inhibit the growth of lithium dendrites and the volume expansion during lithium deposition and desorption, and thus effectively improve the coulomb efficiency and cycle life of the lithium metal negative electrode.
[0057] In some embodiments of the present application, the first polymer is at least one of polyacrylonitrile, polyvinyl pyrrolidone, polyvinylidene fluoride, polycaprolactone, polyurethane, silk fibroin, polyamide, polyvinyl alcohol, polymethyl methacrylate, and asphalt; and / or,
[0058] The solvent of the core solution is at least one of water, ethanol, NN dimethylformamide, acetone, NN diethylacetamide, formic acid, tetrahydrofuran, isopropanol, and hexafluoroisopropanol; and / or,
[0059] In the core solution, the mass ratio of the first polymer to the solvent of the core solution is 1:5-12.
[0060] It is easy to understand that the above-mentioned polymer materials, when used as the first polymer, are all suitable for the electrospinning process and are raw materials with good electrospinning effects. Moreover, the above-mentioned polymers can be easily carbonized to form carbon fibers through heat treatment.
[0061] It is easy to understand that the beneficial effect of the mass ratio of the first polymer to the solvent of the core solution being 1:5-12 is that it ensures that the fibers formed by coaxial electrospinning can be better formed and that the first polymer can be fully dispersed in the core solution.
[0062] As an example, the mass ratio of the first polymer to the solvent of the core solution may be 1:5, 1:7, 1:9, 1:10, or 1:12.
[0063] In some embodiments of the present application, the second polymer is at least one of polyacrylonitrile, polyvinyl pyrrolidone, polyvinylidene fluoride, polycaprolactone, polyurethane, silk fibroin, polyamide, polyvinyl alcohol, polymethyl methacrylate, and asphalt; and / or,
[0064] The solvent of the shell solution is at least one of water, ethanol, NN dimethylformamide, acetone, NN diethylacetamide, formic acid, tetrahydrofuran, isopropanol, and hexafluoroisopropanol; and / or,
[0065] In the shell solution, the mass ratio of the second polymer to the salt substance is 1:0.8-1.2; and / or,
[0066] In the shell solution, the mass ratio of the second polymer to the solvent of the shell solution is 1:4-6.
[0067] It is easy to understand that the above-mentioned polymer materials, when used as the second polymer, are all suitable for the electrospinning process and are raw materials with good electrospinning effects. Moreover, the above-mentioned polymers can be easily carbonized to form carbon fibers through heat treatment.
[0068] It is easy to understand that the beneficial effect of the mass ratio of the second polymer to the salt substance being 1:0.8-1.2 is that the shell structure contains a large amount of metal ions without affecting the molding of the shell structure. On this basis, the beneficial effect of the mass ratio of the second polymer to the solvent of the shell solution being 1:4-6 is that it ensures that the fiber formed by coaxial electrospinning can be well molded and that the salt substance can be well dispersed in the shell solution.
[0069] As an example, the mass ratio of the second polymer to the salt substance may be 1:0.8, 1:0.9, 1:1, 1:1.1, or 1:1.2.
[0070] As an example, the mass ratio of the second polymer to the solvent of the shell solution may be 1:4, 1:4.5, 1:5, 1:5.5, or 1:6.
[0071] In some embodiments of the present application, the coaxial electrospinning is performed by at least one coaxial spinning needle, and averaged to each coaxial spinning needle, the process parameters of the coaxial electrospinning meet the following conditions:
[0072] Voltage is 12~20kV;
[0073] The total liquid feeding rate of the core solution and the shell solution is 0.6-1.5 mL / h;
[0074] The feeding rate ratio of the core solution to the shell solution is 1:1;
[0075] The receiving distance is 12 to 20 cm;
[0076] The duration is 1.8 to 2.2 hours.
[0077] It is easy to understand that the beneficial effect of the voltage of 12 to 20 kV is that the fiber produced by coaxial electrospinning has a smaller diameter while ensuring the molding of the fiber. The beneficial effect of the total liquid feeding rate of the core solution and the shell solution being 0.6 to 1.5 mL / h is to ensure the efficiency of coaxial electrospinning and the molding of the fiber.
[0078] It is easy to understand that the receiving distance is the distance between the liquid outlet end of the coaxial spinneret and the fiber receiving device. The beneficial effects of a receiving distance of 12 to 20 cm are: ensuring sufficient electric field strength during the coaxial electrospinning process; and ensuring that the displacement distance of the core solution and the shell solution to the fiber receiving device is appropriate, so that the fiber receiving device can smoothly collect the fiber, and also allowing the solvent to fully evaporate during the movement of the core solution and the shell solution.
[0079] As an example, the voltage may be 12 kV, 14 kV, 16 kV, 18 kV, 20 kV.
[0080] As an example, the total fluid administration rate may be 0.6 mL / h, 0.8 mL / h, 1 mL / h, 1.3 mL / h, 1.5 mL / h;
[0081] As an example, the receiving distance may be 12 cm, 14 cm, 16 cm, 18 cm, or 20 cm.
[0082] In some embodiments of the present application, the temperature of the carbonization treatment is 700-900° C.; and / or,
[0083] The carbonization treatment time is 1 to 3 hours; and / or,
[0084] The carbonization treatment is performed in an inert atmosphere.
[0085] It is easy to understand that the beneficial effect of the carbonization treatment temperature being 700-900° C. is to save energy as much as possible while ensuring the carbonization effect.
[0086] It is easy to understand that the beneficial effect of the carbonization treatment time of 1 to 3 hours is to save energy as much as possible while ensuring the carbonization effect.
[0087] As an example, the temperature of the carbonization treatment may be 700°C, 750°C, 800°C, 850°C, or 900°C.
[0088] As an example, the carbonization treatment time can be 1 h, 1.5 h, 2 h, 2.5 h, or 3 h.
[0089] In some embodiments of the present application, before the fiber membrane is carbonized, the method further comprises the following steps:
[0090] S20: performing a pre-oxidation treatment on the fiber membrane.
[0091] It is easy to understand that pre-oxidation treatment of the fiber membrane can introduce oxygen-containing groups into the fiber membrane, so that there are sufficient oxygen atoms involved in the subsequent carbonization treatment, thereby making the carbonization treatment more sufficient and thorough.
[0092] In some embodiments of the present application, the temperature of the pre-oxidation treatment is 200-300° C.; and / or,
[0093] The pre-oxidation treatment time is 0.5 to 1 hour; and / or,
[0094] The pre-oxidation treatment is performed in an oxygen-containing atmosphere.
[0095] It is easy to understand that the beneficial effect of the pre-oxidation treatment temperature being 200-300° C. is that it can effectively introduce oxygen-containing groups into the fiber membrane without destroying the structure of the fibers in the fiber membrane.
[0096] It is easy to understand that the beneficial effect of the pre-oxidation treatment time of 0.5 to 1 hour is that it can effectively introduce oxygen-containing groups into the fiber membrane without destroying the structure of the fibers in the fiber membrane.
[0097] In some embodiments of the present application, the temperature of the heat treatment is 400-700° C.; and / or,
[0098] The heat treatment time is 1 to 3 hours.
[0099] It is easy to understand that the beneficial effect of the heat treatment temperature of 400-700° C. is that it can both make the metal ions react with ammonia as much as possible and save energy as much as possible.
[0100] It is easy to understand that the beneficial effect of the heat treatment time of 1 to 3 hours is that the reaction between the metal ions and ammonia can be carried out as fully as possible while saving energy consumption as much as possible.
[0101] As an example, the temperature of the heat treatment may be 400°C, 500°C, 600°C, or 700°C.
[0102] As an example, the heat treatment time can be 1 h, 1.5 h, 2 h, 2.5 h, or 3 h.
[0103] In some embodiments of the present application, the step of preparing lithium metal on the surface of the current collector comprises the following steps:
[0104] S41: In an inert atmosphere, immersing the current collector into molten lithium metal.
[0105] It is easy to understand that the beneficial effect of preparing lithium metal on the surface of the current collector by immersing molten lithium metal is that the molten lithium metal can penetrate into the surface layer of the fibers of the current collector, thereby more firmly bonding to the current collector, and the temperature conditions and inert atmosphere conditions required for immersing molten lithium metal are easy to provide, and the equipment requirements are not high.
[0106] In a second aspect, an embodiment of the present application provides a lithium battery, wherein the lithium battery comprises a lithium battery negative electrode prepared by the method described in any embodiment of the first aspect.
[0107] The lithium battery is realized based on the lithium battery negative electrode described in any embodiment of the first aspect. The specific implementation of the lithium battery can refer to the above embodiments and common knowledge in the field. Since the lithium battery adopts part or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0108] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0109] Example 1
[0110] This embodiment provides a method for preparing a negative electrode of a lithium battery, the method comprising the following steps:
[0111] Coaxial electrospinning is performed with a core solution and a shell solution to obtain a fiber membrane;
[0112] The fiber membrane is subjected to a pre-oxidation treatment and a carbonization treatment in sequence to obtain a carbon fiber membrane;
[0113] heat-treating the carbon fiber film in an ammonia atmosphere to obtain a current collector;
[0114] In a nitrogen atmosphere, immersing the current collector in molten lithium metal for 5 minutes to prepare lithium metal on the surface of the current collector to obtain a prefabricated negative electrode;
[0115] The prefabricated negative electrode is pressed to obtain the negative electrode of the lithium battery.
[0116] Among them, the fibers of the fiber membrane have a core structure and a shell structure, the shell structure covers the core structure, the core solution is used to form the core structure during the coaxial electrospinning process, and the shell solution is used to form the shell structure during the coaxial electrospinning process, the core solution includes a carbonizable first polymer, the shell solution includes a salt substance and a carbonizable second polymer, and the metal element of the salt substance is at least one of chromium, nickel, cobalt, manganese, iron, copper, molybdenum, and zinc.
[0117] In some embodiments of the present application, the first polymer is polyacrylonitrile, the solvent of the core solution is tetrahydrofuran, and in the core solution, the mass ratio of the first polymer to the solvent of the core solution is 1:5.
[0118] In some embodiments of the present application, the second polymer is polyacrylonitrile, the solvent of the shell solution is tetrahydrofuran, and in the shell solution, the mass ratio of the second polymer to the salt substance is 1:0.8, and in the shell solution, the mass ratio of the second polymer to the solvent of the shell solution is 1:4.
[0119] In some embodiments of the present application, the temperature of the carbonization treatment is 700° C., the time of the carbonization treatment is 3 hours, and the carbonization treatment is performed in a nitrogen atmosphere.
[0120] In some embodiments of the present application, the temperature of the pre-oxidation treatment is 200° C., the time of the pre-oxidation treatment is 1 hour, and the pre-oxidation treatment is performed in air.
[0121] In some embodiments of the present application, the temperature of the heat treatment is 400° C., and the time of the heat treatment is 3 hours.
[0122] In some embodiments of the present application, the coaxial electrospinning is performed by a single coaxial spinning needle, and the process parameters of the coaxial electrospinning meet the following conditions:
[0123] The voltage is 12kV;
[0124] The spinning solution flow rate was 0.6 mL / h;
[0125] The receiving distance is 12cm;
[0126] The duration of the coaxial electrospinning was 2 h.
[0127] In this embodiment, the negative electrode of the lithium battery is in the form of a foil, and the thickness of the negative electrode of the lithium battery is 10 μm.
[0128] Example 2
[0129] This embodiment provides a method for preparing a negative electrode of a lithium battery, the method comprising the following steps:
[0130] Coaxial electrospinning is performed with a core solution and a shell solution to obtain a fiber membrane;
[0131] The fiber membrane is subjected to a pre-oxidation treatment and a carbonization treatment in sequence to obtain a carbon fiber membrane;
[0132] heat-treating the carbon fiber film in an ammonia atmosphere to obtain a current collector;
[0133] In a nitrogen atmosphere, immersing the current collector in molten lithium metal for 5 minutes to prepare lithium metal on the surface of the current collector to obtain a prefabricated negative electrode;
[0134] The prefabricated negative electrode is subjected to a rolling process to obtain the negative electrode of the lithium battery.
[0135] Among them, the fibers of the fiber membrane have a core structure and a shell structure, the shell structure covers the core structure, the core solution is used to form the core structure during the coaxial electrospinning process, and the shell solution is used to form the shell structure during the coaxial electrospinning process, the core solution includes a carbonizable first polymer, the shell solution includes a salt substance and a carbonizable second polymer, and the metal element of the salt substance is at least one of chromium, nickel, cobalt, manganese, iron, copper, molybdenum, and zinc.
[0136] In some embodiments of the present application, the first polymer is polyvinyl pyrrolidone, the solvent of the core solution is acetone, and in the core solution, the mass ratio of the first polymer to the solvent of the core solution is 1:12.
[0137] In some embodiments of the present application, the second polymer is polyurethane, the solvent of the shell solution is NN diethylacetamide, in the shell solution, the mass ratio of the second polymer to the salt substance is 1:1.2, and in the shell solution, the mass ratio of the second polymer to the solvent of the shell solution is 1:6.
[0138] In some embodiments of the present application, the temperature of the carbonization treatment is 900° C., the time of the carbonization treatment is 1 hour, and the carbonization treatment is performed in a nitrogen atmosphere.
[0139] In some embodiments of the present application, the temperature of the pre-oxidation treatment is 300° C., the time of the pre-oxidation treatment is 0.5 h, and the pre-oxidation treatment is performed in air.
[0140] In some embodiments of the present application, the temperature of the heat treatment is 700° C., and the time of the heat treatment is 1 hour.
[0141] In some embodiments of the present application, the coaxial electrospinning is performed by a single coaxial spinning needle, and the process parameters of the coaxial electrospinning meet the following conditions:
[0142] The voltage is 20kV;
[0143] The spinning solution flow rate was 1.5 mL / h;
[0144] The receiving distance is 20cm;
[0145] The duration of the coaxial electrospinning was 2 h.
[0146] In this embodiment, the negative electrode of the lithium battery is in the form of a foil, and the thickness of the negative electrode of the lithium battery is 30 μm.
[0147] Example 3
[0148] This embodiment provides a method for preparing a negative electrode of a lithium battery, the method comprising the following steps:
[0149] Coaxial electrospinning is performed with a core solution and a shell solution to obtain a fiber membrane;
[0150] The fiber membrane is subjected to a pre-oxidation treatment and a carbonization treatment in sequence to obtain a carbon fiber membrane;
[0151] heat-treating the carbon fiber film in an ammonia atmosphere to obtain a current collector;
[0152] In a nitrogen atmosphere, immersing the current collector in molten lithium metal for 5 minutes to prepare lithium metal on the surface of the current collector to obtain a prefabricated negative electrode;
[0153] The prefabricated negative electrode is pressed to obtain the negative electrode of the lithium battery.
[0154] Among them, the fibers of the fiber membrane have a core structure and a shell structure, the shell structure covers the core structure, the core solution is used to form the core structure during the coaxial electrospinning process, and the shell solution is used to form the shell structure during the coaxial electrospinning process, the core solution includes a carbonizable first polymer, the shell solution includes a salt substance and a carbonizable second polymer, and the metal element of the salt substance is at least one of chromium, nickel, cobalt, manganese, iron, copper, molybdenum, and zinc.
[0155] In some embodiments of the present application, the first polymer is polyamide, the solvent of the core solution is NN dimethylformamide, and in the core solution, the mass ratio of the first polymer to the solvent of the core solution is 1:7.
[0156] In some embodiments of the present application, the second polymer is polyvinyl alcohol, the solvent of the shell solution is water, in the shell solution, the mass ratio of the second polymer to the salt substance is 1:1, and in the shell solution, the mass ratio of the second polymer to the solvent of the shell solution is 1:5.
[0157] In some embodiments of the present application, the temperature of the carbonization treatment is 800° C., the time of the carbonization treatment is 2 h, and the carbonization treatment is performed in a nitrogen atmosphere.
[0158] In some embodiments of the present application, the temperature of the pre-oxidation treatment is 240° C., the time of the pre-oxidation treatment is 0.8 h, and the pre-oxidation treatment is performed in air.
[0159] In some embodiments of the present application, the temperature of the heat treatment is 500° C., and the time of the heat treatment is 1.5 h.
[0160] In some embodiments of the present application, the coaxial electrospinning is performed by a single coaxial spinning needle, and the process parameters of the coaxial electrospinning meet the following conditions:
[0161] The voltage is 18kV;
[0162] The spinning solution flow rate was 1 mL / h;
[0163] The receiving distance is 17cm;
[0164] The duration of the coaxial electrospinning was 2 h.
[0165] In this embodiment, the negative electrode of the lithium battery is in the form of a foil, and the thickness of the negative electrode of the lithium battery is 20 μm.
[0166] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0167] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "including", "comprising", etc. refer to "including but not limited to". Moreover, the terms "including", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "including..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. For the association relationship of more than three associated objects described by "and / or", it means that any one of these three associated objects can exist alone, or any at least two of them exist at the same time. For example, for A, and / or B, and / or C, it can be represented that any one of A, B, and C exists alone, or any two of them exist at the same time, or three of them exist at the same time. In this article, "at least one" refers to one or more, and "multiple" refers to two or more. "At least one", "the following at least one (individual)" or similar expressions refer to any combination of these items, including any combination of single items (individuals) or plural items (individuals). For example, "at least one (individual) of a, b, or c", or "at least one (individual) of a, b, and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, wherein a, b, c can be single or multiple respectively. The "number of parts" involved in this application, such as weight parts, mass parts, etc., represent the proportional relationship between each component. In the proportional relationship involved in the present application, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, if the mass ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond one-to-one with the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.
[0168] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a negative electrode of a lithium battery, characterized in that: The method comprises the following steps Coaxial electrospinning is performed with a core solution and a shell solution to obtain a fiber membrane; Carrying out carbonization treatment on the fiber membrane to obtain a carbon fiber membrane; heat-treating the carbon fiber film in an ammonia atmosphere to obtain a current collector; preparing lithium metal on the surface of the current collector to obtain a prefabricated negative electrode; The prefabricated negative electrode is pressed to obtain the negative electrode of the lithium battery. Among them, the fibers of the fiber membrane have a core structure and a shell structure, the shell structure covers the core structure, the core solution is used to form the core structure during the coaxial electrospinning process, and the shell solution is used to form the shell structure during the coaxial electrospinning process, the core solution includes a carbonizable first polymer, the shell solution includes a salt substance and a carbonizable second polymer, and the metal element of the salt substance is at least one of chromium, nickel, cobalt, manganese, iron, copper, molybdenum, and zinc.
2. The method for preparing a negative electrode of a lithium battery according to claim 1, characterized in that: The first polymer is at least one of polyacrylonitrile, polyvinyl pyrrolidone, polyvinylidene fluoride, polycaprolactone, polyurethane, silk fibroin, polyamide, polyvinyl alcohol, polymethyl methacrylate, and asphalt; and / or, The solvent of the core solution is at least one of water, ethanol, NN dimethylformamide, acetone, NN diethylacetamide, formic acid, tetrahydrofuran, isopropanol, and hexafluoroisopropanol; and / or, In the core solution, the mass ratio of the first polymer to the solvent of the core solution is 1:5-12.
3. The method for preparing a negative electrode of a lithium battery according to claim 1, characterized in that: The second polymer is at least one of polyacrylonitrile, polyvinyl pyrrolidone, polyvinylidene fluoride, polycaprolactone, polyurethane, silk fibroin, polyamide, polyvinyl alcohol, polymethyl methacrylate, and asphalt; and / or, The solvent of the shell solution is at least one of water, ethanol, NN dimethylformamide, acetone, NN diethylacetamide, formic acid, tetrahydrofuran, isopropanol, and hexafluoroisopropanol; and / or, In the shell solution, the mass ratio of the second polymer to the salt substance is 1:0.8-1.2; and / or, In the shell solution, the mass ratio of the second polymer to the solvent of the shell solution is 1:4-6.
4. The method for preparing a negative electrode of a lithium battery according to claim 1, characterized in that: The coaxial electrospinning is performed by at least one coaxial spinning needle. On average, for each coaxial spinning needle, the process parameters of the coaxial electrospinning meet the following conditions: Voltage is 12~20kV; The spinning solution flow rate is 0.6-1.5 mL / h; The receiving distance is 12 to 20 cm; The duration is 1.8 to 2.2 hours.
5. The method for preparing a negative electrode of a lithium battery according to claim 1, characterized in that: The temperature of the carbonization treatment is 700-900° C.; and / or, The carbonization treatment time is 1 to 3 hours; and / or, The carbonization treatment is performed in an inert atmosphere.
6. The method for preparing a negative electrode of a lithium battery according to claim 1, characterized in that: Before the fiber membrane is carbonized, the method further comprises the following steps: The fiber membrane is subjected to a pre-oxidation treatment.
7. The method for preparing a negative electrode for a lithium battery according to claim 6, characterized in that: The temperature of the pre-oxidation treatment is 200-300° C.; and / or, The pre-oxidation treatment time is 0.5 to 1 hour; and / or, The pre-oxidation treatment is performed in an oxygen-containing atmosphere.
8. The method for preparing a negative electrode for a lithium battery according to claim 1, characterized in that: The heat treatment temperature is 400-700° C.; and / or, The heat treatment time is 1 to 3 hours.
9. The method for preparing a negative electrode for a lithium battery according to claim 1, characterized in that: The step of preparing lithium metal on the surface of the current collector comprises the following steps: The current collector is immersed in molten lithium metal in an inert atmosphere.
10. A lithium battery, characterized in that: The lithium battery comprises a lithium battery negative electrode prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Self-supporting lithium metal negative electrode material and preparation method and application thereof
CN112054203A
Carbon nanofiber composite material with three-dimensional hierarchical structure and preparation method thereof
CN113363083A
Composite negative electrode, preparation method thereof and application of composite negative electrode in metal secondary battery
CN116247163A
Method for preparing monatomic manganese / lithium composite negative electrode by mechanical rolling
CN117199228A
Hollow ceramic fiber and its production
JP1994294019A